Kualitas Fisik Silase Rumput Gajah (Pennisetum Purpureum) dengan Penambahan Air Tape Ketan - Rini Rida Jayanti; Irine Ike Praptiwi; Maria M N N Lesik (Faculty of Agriculture, Musamus University, 2023)
This study aims to determine how adding glutinous tapai water affects physical quality in the silage process of Elephant Grass (Pennisetum purpureum). The method used in this study was a Complete Randomized Design (RAL) with 4 treatments and 3 repeats. The treatment used includes P0: tapai water 0%, P1: tapai water 3%, P2: tapai water 6%, P3: tapai water 9%. The study was conducted through several stages, including preparation of glutinous rice tapai water, preparation of elephant grass, making silage, observation of silage results carried out by respondents using questionnaires, and analysis. The parameters of physical qualities observed include colour, aroma, texture and presence of mushroom. The results obtained are P3 treatment (the use of 9% tapai water) has a real effect on the colour, aroma, texture and presence of mushrooms. Respondents prefer silage with better P3 treatment than other treatments. The P3 treatment showed the absence of mushrooms, while in other treatments (P0, P1 and P2) silage fermented for 21 days showed the presence of mushrooms.